Natural radioactivity and hazard assessment of imported ceramic tiles in Nigeria (2009)
The natural radionuclides (226Ra, 232Th and 40K) content of ceramic wall and floor tiles commonly used in Nigeria have been determined by a gamma ray spectroscopy system using a high purity germanium detector. The activity concentrations of 226Ra, 232Th and 40K ranged from 52 ± 2 to 105 ± 3, 56 ± 1 to 115 ± 2 and 185 ± 9 to 893 ± 17 Bq kg-1 with mean values of 72 ± 14, 84 ± 18 and 629 ± 198 Bq kg-1, respectively for the wall tiles. For the floor tiles, the activity concentrations of 226Ra, 232Th and 40K varied from 41 ± 2 to 131 ± 4, 59 ± 1 to 127 ± 2 and 351 ± 11 to 979 ± 16 Bq kg-1 with mean values of 74 ± 31, 82 ± 24 and 618 ± 231 Bq kg-1, respectively. The errors quoted in the means are standard deviations. The values of radium equivalent activity (Raeq) calculated varied from 194 to 328 Bq kg-1 for the wall tiles, and 176 to 306 Bq kg-1 for the floor tiles. The radium equivalent activities of all the samples examined were lower than the recommended limit of 370 Bq kg-1 for building materials. The mean values of the external hazard index (Hex), the activity index (Iγ) and the alpha index (Iα) of the wall and floor tiles are less than unity, which is a commonly accepted limit.